The Bear and Her Book - O'Connor, Sophia; Tosdevin, Frances (Mendota Heights, MN : Jolly Fish Press, 2023)
"A book-loving bear sets off to see the world and discovers the magical places that books can take her"--
Grades K-1
Keywords: Bears -- Fiction; Books and reading -- Fiction; Animals -- Fiction; Picture books